Outcome of serious violent offenders with psychotic illness and cognitive disorder dealt with by the New South Wales criminal justice system. (May 2019) - Nielssen, Olav; Yee, Natalia YL; Dean, Kimberlie; Large, Matthew
Background: The few studies of the recidivism by people with psychotic illness and cognitive disorder who are convicted of serious violent offences and sentenced by the courts. Method: Re-imprisonment data were obtained for 661 individuals convicted of serious non-lethal violent offences in the District Courts of New South Wales in the years 2006 and 2007. Rates of re-imprisonment of offenders known to psychotic illness or cognitive disorder (intellectual disability or acquired brain injury) was compared to those not known to have those conditions. A survival analysis was performed controlling for the effects of male sex, having a report by a mental health professional at the initial sentencing and receiving a custodial sentence for the initial offence. Results: There was no significant difference in the overall likelihood of further imprisonment between those with psychotic disorder (53.7%), those with cognitive disorder (50.7%) or among those with neither condition (45.2%; χ 2 = 2.22, p = 0.33). A Kaplan–Meier analysis found that people with a psychotic disorder were returned to custody earlier than those not known to have psychosis ( p = 0.002). People with psychosis spent a non-significantly greater time in custody (mean 477 days) than those with a cognitive disorder (mean 334 days) or among those with neither condition (mean 348 days) (Mann–Whitney Z -score = 1.5, η 2 = 0.003, p value = 0.13). For the entire sample of 661 offenders, those who received non-custodial sentences for their initial offences had a lower likelihood of spending any time in custody in the follow-up period. Conclusion: The likelihood of returning to custody of sentenced violent offenders with psychotic illness or cognitive disorder is higher than that of released forensic patients in New South Wales followed up for a similar period. The results suggest an opportunity to improve the outcome of offenders with psychosis by better treatment and rehabilitation.